Analysis of Monocyte/Lymphocyte Ratio and Monocyte/HDL Ratio as A Predictor of Mortality in ACS - Nanda Amelia; Tenri Esa; Darmawaty E Rauf (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Inflammatory process plays a role in the prognosis and development of Acute Coronary Syndrome (ACS). Inflammation parameters associated with ACS mortality are Monocyte/Lymphocyte ratio (MLR) and Monocyte/High Density Lipoprotein ratio (MHR). This study aimed to analyze MLR and MHR as predictors of ACS mortality based on the GRACE score. A cross-sectional retrospective study on ACS patients at Dr. Wahidin Sudirohusodo Makassar for the period January 2019-December 2020. Acute coronary syndrome patients were grouped into low, medium and high risk based on the GRACE score. Monocyte/lymphocyte ratio and MHR were measured on admission. The Kolmogorov-Smirnov test, Kruskal-Wallis test, Spearman's correlation test and Receiver Operating Characteristics (ROC) statistical tests were used. The statistical test results were significant if the p-value < 0.05. The sample consisted of 422 ACS patients, 70 low risk patients, 156 medium risk and 196 high risk patients. Age range 30–88 years. The mean MLR 0.50±0.37 and MHR 0.19±0.15. The mean MLR was the highest significant at high risk (0.58) and the lowest at low risk (0.37) (p<0.001); while MHR was not significant. Monocyte/lymphocyte ratio was positively correlated with GRACE score (p < 0.001), while MHR was not correlated (p 0.310). From the MLR ROC curve, the cut-off was 0.35 (AUC 0.673; 95% CI 0.695-0.742). MLR values increase in high-risk patients due to the ongoing inflammatory process. The MHR value did not show a positive correlation with mortality. Monocyte/lymphocyte ratio had a predictive value on mortality with a cut-off of 0.35 while the role of MHR still requires further research.